2015
DOI: 10.1152/ajprenal.00419.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate global maternal nutrient reduction on fetal baboon renal mitochondrial gene expression at 0.9 gestation

Abstract: Pereira SP, Oliveira PJ, Tavares LC, Moreno AJ, Cox LA, Nathanielsz PW, Nijland MJ. Effects of moderate global maternal nutrient reduction on fetal baboon renal mitochondrial gene expression at 0.9 gestation. Am J Physiol Renal Physiol 308: F1217-F1228, 2015. First published March 11, 2015 doi:10.1152/ajprenal.00419.2014.-Early life malnutrition results in structural alterations in the kidney, predisposing offspring to later life renal dysfunction. Kidneys of adults who were growth restricted at birth have su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Sex-dependent changes in renal mitochondrial function were observed in the baboon model of maternal undernutrition [16]. Using a swine model of maternal undernutrition, Gonzalez-Bulnes et al [92] showed that female conceptuses had higher viability rates and lower incidence of severe growth retardation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex-dependent changes in renal mitochondrial function were observed in the baboon model of maternal undernutrition [16]. Using a swine model of maternal undernutrition, Gonzalez-Bulnes et al [92] showed that female conceptuses had higher viability rates and lower incidence of severe growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal low protein diet results in high blood pressure in offspring [10], altered endocrine function [9], immune function [7], and renal development [11]. Same long-term consequences of maternal malnutrition were observed in long-gestation, precocial species including r, sheep [12, 13] and nonhuman primates [14-16]. The pig is currently considered a reliable large animal model for translational research in IUGR as result of deficiencies in maternal nutritional supply or placental development [17].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that this moderate degree of MNR leads to intrauterine growth restriction (IUGR) at term . We have also reported altered development of the placenta, fetal kidney, fetal brain, fetal liver, fetal skeletal muscle, and fetal heart . In postnatal life, these IUGR offspring show cognitive and behavioral changes, accelerated aging of the heart, and a pre‐diabetic metabolic phenotype when compared to controls.…”
Section: Introductionmentioning
confidence: 93%
“…; Cox et al . ; Pereira et al ); however, the majority of our population is experiencing an environment of caloric excess, and the increase in MO is a major cause of concern for the health of offspring from these pregnancies (McCurdy et al . ).…”
Section: Introductionmentioning
confidence: 99%